Determination of a cost-effectiveness threshold for cancer interventions in Iran - Safari, Hossein; Poder, Thomas G.; Afshari, Somayeh; Nahvijou, Azin; Arab-Zozani, Morteza; Moradi, Nasrin; Ameri, Hosein (Frontiers in Oncology, 2022)
Background and Objectives: The estimation of a cost- Effectiveness (CE) threshold from the perspective of those who have experienced a life-threatening disease can provide empirical evidence for health policy makers to make the best allocation decisions on limited resources. The aim of the current study was to empirically determine the CE threshold for cancer interventions from the perspective of cancer patients. Methods: A composite time trade-off (cTTO) task for deriving quality adjusted life-year (QALY) and a double-bounded dichotomous choice (DBDC) approach followed by open-ended question for examining patients’ willingness-to-pay (WTP) were performed using face-to-face interviews within a nationally representative sample of 565 cancer patients in Iran. The CE threshold was calculated using the nonparametric Turnbull model and parametric interval-censored Weibull regression model. Furthermore, the factors that affect the CE threshold were determined using the parametric model. Results: The estimated CE threshold using the nonparametric Turnbull model and parametric interval-censored Weibull regression model was IRR 440,410,000 (USD 10,485.95) and IRR 595,280,000 (USD 14,173.33) per QALY, respectively. Gender, age, education, income, type of cancer, and current treatment status were significantly associated with the estimated CE threshold. Conclusions: The value of parametric model-based threshold in this study was 1.98 times the Iranian GDP per capita, which was lower than the CE threshold value recommended by the WHO (i.e., 3 times the GDP per capita) for low-and middle-income countries.